A numerical study of the hemodynamic behavior and gas transport in cardiovascular systems with severe cardiac or cardiopulmonary failure supported by venoarterial extracorporeal membrane oxygenation - Cui, Wenhao; Wang, Tianqi; Xu, Zhuoming; Liu, Jinlong; Simakov, Sergey; Liang, Fuyou (Frontiers in Bioengineering and Biotechnology, 2023)
Venoarterial extracorporeal membrane oxygenation (VA-ECMO) has been extensively demonstrated as an effective means of bridge-to-destination in the treatment of patients with severe ventricular failure or cardiopulmonary failure. However, appropriate selection of candidates and management of patients during ECMO support remain challenging in clinical practice, due partly to insufficient understanding of the complex influences of ECMO support on the native cardiovascular system. In addition, questions remain as to how central and peripheral VA-ECMO modalities differ with respect to their hemodynamic impact and effectiveness of compensatory oxygen supply to end-organs. In this work, we developed a computational model to quantitatively address the hemodynamic interaction between the ECMO and cardiovascular systems and associated gas transport. Model-based numerical simulations were performed for cardiovascular systems with severe cardiac or cardiopulmonary failure and supported by central or peripheral VA-ECMO. Obtained results revealed that: 1) central and peripheral VA-ECMO modalities had a comparable capacity for elevating arterial blood pressure and delivering oxygenated blood to important organs/tissues, but induced differential changes of blood flow waveforms in some arteries; 2) increasing the rotation speed of ECMO pump (ω) could effectively improve arterial blood oxygenation, with the efficiency being especially high when ω was low and cardiopulmonary failure was severe; 3) blood oxygen indices (i.e., oxygen saturation and partial pressure) monitored in the right radial artery could be taken as surrogates for diagnosing potential hypoxemia in other arteries irrespective of the modality of ECMO; and 4) left ventricular (LV) overloading could occur when ω was high, but the threshold of ω for inducing clinically significant LV overloading depended strongly on the residual cardiac function. In summary, the study demonstrated the differential hemodynamic influences while comparable oxygen delivery performance of the central and peripheral VA-ECMO modalities in the management of patients with severe cardiac or cardiopulmonary failure and elucidated how the status of arterial blood oxygenation and severity of LV overloading change in response to variations in ω. These model-based findings may serve as theoretical references for guiding the application of VA-ECMO or interpreting in vivo measurements in clinical practice.